2015
DOI: 10.3171/2014.12.jns141687
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to Gamma Knife radiosurgery for intracranial meningiomas

Abstract: M eningioMas are the most common primary intracranial nonglial neoplasms in adults. 34 When feasible, the ideal management of meningiomas is complete resection of the tumor and associated dura mater, with the goal of minimizing further neurological morbidity for the patient. 28 However, not all meningiomas are amenable to gross-total resection (e.g., extensive involvement of skull base structures or invasion into the venous sinuses or other neurovascular structures), and alternative complementary treatment str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…GKRS effectively controls the growth of meningiomas with a control rate of 85% to 99% at follow-ups of more than 3 years. 4,7,15 Our results are consistent with current data. In total, 89% (n = 23) of meningiomas did not progress after a mean control period of 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…GKRS effectively controls the growth of meningiomas with a control rate of 85% to 99% at follow-ups of more than 3 years. 4,7,15 Our results are consistent with current data. In total, 89% (n = 23) of meningiomas did not progress after a mean control period of 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…9,15,25 Some recent studies that were focused on the treatment of intracranial meningiomas with radiosurgery reported that the local tumor control rates ranged from 88% to 100%, in which 19%-74% of tumors shrank during a mean follow-up of 36-78 months. 3,7,12,21,22,[30][31][32][33][34]37,[39][40][41] In a single-center study, Hasegawa et al 12 reported an actuarial PFS rate of 92%, 86%, and 72% at 3, 5, and 10 years, respectively, in 67 patients. In a meta-analysis of SRS for skull base meningiomas, Starke et al 41 reviewed the outcome in 469 patients with large skull base meningiomas (> 8 cm) from several centers, and reported that the actuarial tumor PFS rates at 3, 5, and 10 years were 90.3%, 88.6%, and 77.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…30 Categorized by tumor site, the percentages were as follows: convexity meningiomas (16.7%), parafalcine and parasagittal meningiomas (17.9%), sellar and parasellar meningiomas (17.3%), petroclival meningiomas (14.7%), cerebellopontine angle (CPA) meningiomas (13.5%), tentorial meningiomas (10.2%), foramen magnum meningiomas (1.3%), sphenoidal meningiomas (6.4%), and olfactory meningiomas (1.9%). 21,22,41 There were 73 (46.8%) residual or progressive tumors with a median volume of 8.9 cm 3 (range 0.33-45.78 cm 3 ), and 83 (53.2%) initial tumors with a median volume of 2.6 cm 3 (range 0.23-21.1 cm 3 ).…”
Section: Patient and Tumor Attributesmentioning
confidence: 99%
“…Table 1 summarizes 26 published studies (all single-or multi-institutional retrospective analyses), listing the studies' meningioma sites, SRS treatment modality, endpoints analyzed, crude risks of edema, and timing of the onset of edema; more detailed information is provided in Tables E1 and E2 (available online at www.redjournal.org). In these tables, studies are grouped as follows (1) those with all non-BOS meningiomas (10)(11)(12)(13)(14)(15)(16)(17)(18), (2) those that separated out non-BOS meningiomas in the crude risks of edema (19)(20)(21)(22)(23)(24)(25)(26)(27), and (3) those did not separate out non-BOS meningiomas in the crude risks of edema (3,(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%